Muhasebenin Yönetim Aracı Olarak Kullanımı - (:unkn) unknown (My University, 2002)
0

Currently cost and managerial accounting is being evaluated by the functions of planning, controlling, decision making and other managerial functions. Managerial accounting has become an important itself with management, economy, operational research and statistics. As a result of these changes in managerial accounting; value based management, just in time, total quality management, logistics, activity based costing, life cycle costing, target costing has become more important.